Fertility Outcome after Operative Laparoscopy versus No Treatment in Infertile Women with Minimal or Mild Endometriosis - Ashraf Moini (International Journal of Fertility and Sterility, 2012)
Background Endometriosis is the presence of endometrial glands and stroma in sites other than the uterine cavity, which is associated with infertility. The objective of this study was to evaluate the effect of laparoscopic surgical treatment on clinical pregnancy in infertile women with minimal or mild endometriosis. Materials and Methods This clinical trial study was performed in infertile women who were referred to the gynecological clinic between April 2008 and March 2009. After confirmation of minimal or mild endometriosis by diagnostic laparoscopy, patients were randomly assigned into two groups using consecutively numbered, opaque sealed envelops. The first group consisted of women who only underwent diagnostic laparoscopy (no treatment) before randomization. The second group of patients underwent operative laparoscopies. T-test and chi-square test were used when appropriate. A p-value less than 0.05 was considered statistically significant. Results Analysis with 38 patients in each group showed characteristics such as age, body mass index (BMI), and duration of infertility were statistically similar in both groups. At 9 months follow- up, 9 (24%) women who had operative laparoscopies became pregnant compared with 7 (18%) women in the diagnostic laparoscopy group. The pregnancy rate showed no statistically significant difference between both groups (p=0.49). No complications were reported in either group. Conclusion The present study suggested that laparoscopic surgical treatment was not superior to diagnostic laparoscopy in pregnancy occurrence in infertile women with minimal and mild endometriosis. (IRCT Number: IRCT201012311952N2).